Ausrichtung, Abstimmung, Einsatz durch Leadership bessere Ergebnisse erzielen - McCauley, Cynthia D. 1958-; Fick-Cooper, Lynn (Center for Creative Leadership, 2018)
If your team isn't getting results, you may think the problem starts with a failure in leadership. While the person in charge may have issues, a leadership problem doesn't necessarily mean you have a "leader" problem. Leadership is not just about the people at the top, but is a social process, enabling individuals to work together as a cohesive group to produce collective results. This book will show you how to diagnose problems in your team by focusing on the three outcomes of effective leadership: direction, alignment, and commitment. By assessing where your group stands in each of these outcomes, you can plan and implement the changes necessary to get better results.
Includes bibliographical references. - Online resource; title from PDF title page (EBSCO, viewed October 24, 2018)
Keywords: Leadership; Management; Gestion; management; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior